Analisis Nilai Kemandirian Siswa pada Pembelajaran Daring - Anggereni, Desi Tri; Sasongko, Rambat Nur; Kristiawan, Muhammad; Riyanto, Muklis; Susanto, Edy (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine self-regulated students in participating in the instructional process in the network (online) in TK IT Al Mawaddah Muara Rupit. The research method used is descriptive quantitative method in the form of a survey that uses a questionnaire as an instrument of data collection and data analysis techniques are descriptive statistics. The sample in this study were 27 respondents. The sample was taken by using purposive sampling technique. The results of the study, 81.5% of students were independent to wake up by themselves and then make the bed. 100% of students bathe themselves and wear their own clothes without the help of their parents, 70.4% of students remember today's lesson without being reminded by their parents, 77.8% of students do their own schoolwork, and 74.1% of students do their schoolwork on time without parents reminded. Even so, there are still students who do not have much independence to carry out all their activities so they still need help from their parents. In conclusion, the independence of students at TK IT Al Mawaddah Muara Rupit in online learning is good enough because almost all students are starting to become aware of the independence that must be done as students or early childhood. Keyword: Analyze, Student Independence, online instructional.